Pengaruh Ukuran Perusahaan, Profitabilitas, Solvabilitas, dan Kebijakan Dividen Terhadap Nilai Perusahaan - Hikmah Etikasari; Eny Maryanti (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
This study aims to determine whether company size, profitability ratio, solvency ratio, and dividend policy on firm value in consumer goods industry companies listed on the Indonesia Stock Exchange (IDX). The period of this research is 2016-2019. The research population includes all food and beverage sub-sector consumer goods companies listed on the Indonesia Stock Exchange (BEI) for the 2016-2019 period. The sampling technique used was purposive sampling technique. The research population data were 112 companies, and obtained a sample of 40 companies. The data analysis method used is the classical assumption test, multiple linear regression, hypothesis testing, and the coefficient of determination (R2) with the help of the SPSS (Statistical Package for the Social Sciences) program version 25. The results of this study indicate: company size has a positive and significant effect on firm value, the profitability ratio proxied by ROI (Return on Investment) has a positive and significant effect on firm value, the solvency ratio proxied by DAR (Debt to Total Assets) has a positive and significant effect. on firm value, and dividend policy as measured by DYD (Dividend Yield) has a negative and significant effect on firm value.